Diastereoselective Synthesis of NH-Unprotected Spiropyrrolidines via the Huisgen Reaction of Acenaphthoquinone-Derived Azomethine Ylides with β-Nitrostyrenes - Yavari, Issa; Ghafouri, Kiyana (Synthesis, 2024)
4′-Nitro-2H-spiro[acenaphthylene-1,2′-pyrrolidine]-2-one derivatives are prepared via [3+2] cycloaddition reactions of azomethine ylides, generated in situ from acenaphthoquinone and primary amines, with β-nitrostyrenes in the presence of (iPr)2NEt in methanol. Evidence for the structures of the products was obtained from single-crystal X-ray analysis. The important feature of this diastereoselective synthesis of NH-unprotected spiropyrrolidines is the formation of four contiguous stereogenic centers, one of which is quaternary, with high selectivity.
Keywords: azomethine ylide; Huisgen reaction; spiro compound; β-nitrostyrenes; acenaphthoquinone